Answer:
-The answer for the radius:
[tex]\sqrt{61} = r[/tex]
Step-by-step explanation:
-The equation of a circle is:
[tex](x-h)^2+(y-k)^2=r^2[/tex] (where the center is known as [tex](h,k)[/tex], the point is [tex](x,y)[/tex] and the radius known as [tex]r[/tex]).
-Use both the center (-2,-1) and the point (-7,-7) for the equation:
[tex](-7+2)^2+(-7+1)^2=r^2[/tex]
-Then, solve the equation to get the radius:
[tex](-7+2)^2+(-7+1)^2=r^2[/tex]
[tex](-5)^2+(-6)^2=r^2[/tex]
[tex]25+36=r^2[/tex]
[tex]61 = r^2[/tex]
[tex]\sqrt{61} = \sqrt{r^2}[/tex]
[tex]\sqrt{61} =r[/tex]
So, therefore the radius is [tex]\sqrt{61}[/tex] .